Maxwell M. Rabb: a hidden hand of the Eisenhower administration in civil rights and race relations - Zasimczuk, Ivan A. (Kansas State University, 2008)
This work examines Maxwell M. Rabb's role in the area of civil rights and race relations from January 1953 through May 1958 during the administration of President Dwight D. Eisenhower. Rabb was the first Secretary to the Cabinet, a position created by Eisenhower. In his lesser known duty, Max Rabb quietly developed many aspects of President Eisenhower's civil rights program. Chapter One describes Rabb's pivotal role in ending segregation in the military establishment to include the Navy and the Veterans Administration. In this chapter Rabb is a lone operator, personally meeting with principal actors in the Eisenhower Administration and U.S. Congress to end segregation. Chapter Two examines how Rabb participated in and helped to develop the various organizations of the White House. As the organizations within the Eisenhower White House matured, Rabb was able to use them as roads into the problem of civil rights and to use their power to advance civil rights. The final chapter focuses on the confluence of race relations and human rights on the one hand with U.S. domestic and foreign policy on the other. The chapter uses four cases studies to illustrate the growing importance of American race relations in world affairs after World War II. Max Rabb's participation in each case serves as a reminder that the American domestic sphere had become a cause of international concern and could damage the credibility of U.S democratic values in the a world where racial sensitivity was on the rise and increasingly a factor in international relations. This work ends by concluding that Rabb's effectiveness was severely limited by President Eisenhower's narrow understanding of the limits of government. Rabb was a New Deal Republican serving in the administration of a man who rejected the activism required by New Deal Liberalism. Though Rabb served Eisenhower well, it was Eisenhower who failed to sense the full scope of the problems in U.S. civil rights and race relations.
Keywords: Maxwell Rabb; New Deal republicans; Liberalism; Civil rights in the Eisenhower era; Desegregation; U.S. race relations in the cold war; American Studies (0323); History, United States (0337); Political Science, General (0615)